Impact of Small and Medium Enterprises on the Indian Economy - Nair, Anupama (Digital Repository of Theses - SSBM Geneva, 2025)
Small and Medium Enterprises (SMEs) are the backbone of the Indian economy, creating jobs, contributing to industrial production, and export development. This research investigated the multi-faceted impact of SMEs on the Indian economic context and discussed their role in promoting gross domestic product (GDP), innovation, rural industrialization, and inclusivity. With approximately 63 million enterprises involved with manufacturing, services, and trade sectors, SMEs accounted for approximately 30% of GDP and nearly half of all exports. SMEs are important contributors to economic decentralization and are reducing disparities between regions by promoting entrepreneurship in semi-urban and rural regions. The study also investigates the primary barriers facing SMEs, including limited access to finance, weak infrastructure, regulatory burdens, technology gaps, and skills gaps. It studies the efficacy of several government interventions, such as the Credit Guarantee Scheme, Udyam Registration, and Digital MSME Program, in aiding the growth of the sector. In addition, it identifies structural constraints and provides an agenda on policy reform, financial inclusion, digital empowerment, and sustainable business practices. Ultimately, this research highlights that bolstering the SME sector is vital for sustainable economic growth that is inclusive and resilient for the economy of India. It then ends with directions for future research to help enrich understanding of sectoral issues, regional variability, and post-pandemic recovery strategies. Similarly, as the report underscores the critical significance of SMEs in the growth of innovation, self-reliance, and job-led development as a result of the provision of millions of livelihoods, particularly to youth and women, and among disadvantaged groups, SMEs are key to eradicating poverty and encouraging equal access and opportunity. SMEs also enhance competitiveness in worldwide supply chains and to a greater extent in the digital economy. However, for this transformative potential to be realized, there needs to be a supportive ecosystem of coordinated plans by the government, financial institutions, trade associations, and academia, with shared and clear objectives. This includes strengthening infrastructure, improving access to markets, supporting climate-positive practices, and supporting the entrepreneurial spirit more generally, for the future development of India’s SME growth.